Gait impairment-related axonal degeneration in Parkinson’s disease by neurite orientation dispersion and density imaging - Xuan Wei; Shiya Wang; Mingkai Zhang; Ying Yan; Zheng Wang; Wei Wei; Houzhen Tuo; Zhenchang Wang (npj Parkinson's Disease, 2024)
Abstract Microstructural alterations in the brain networks of Parkinson’s disease (PD) patients are correlated with gait impairments. Evaluate microstructural alterations in the white matter (WM) fiber bundle tracts using neurite orientation dispersion and density imaging (NODDI) technique in PD versus healthy controls (HC). In this study, 24 PD patients and 29 HC were recruited. NODDI and high-resolution 3D structural images were acquired for each participant. The NODDI indicators, including the intracellular neurite density index (NDI), orientation dispersion index (ODI), and isotropic volume fraction (ISO), were compared between the two groups. Diffusion-weighted (DW) images were preprocessed using MRtrix 3.0 software and the orientation distribution function to trace the main nerve fiber tracts in PD patients. Quantitative gait and clinical assessment scales were used to compare the medication “ON” and “OFF” states of PD patients. The NDI, ODI, and ISO values of the WM fiber bundles were significantly higher in PD patients compared to HC. Fiber bundles, including the anterior thalamic radiation, corticospinal tract, superior longitudinal fasciculus, forceps major, cingulum, and inferior longitudinal fasciculus, were found to be significantly affected in PD. The NDI changes of PD patients were well correlated with stride lengths in the “ON” state; ODI changes were correlated with the stride time in the “ON” and “OFF” states and ISO changes were correlated with the stride time and cadence in the “ON” state. In conclusion, combination of NODDI technique and gait parameters can help detect gait impairment in PD patients early and accurately.